SALMONELLA CONTROL IN POULTRY PRODUCTION AND RESISTANCE MONITORING IN SERBIA - Maja Velhner; Dubravka Potkonjak; Igor Stojanov; Dragica Stojanović; Jelena Petrović; Gordana Kozoderović (Archives of Veterinary Medicine, 2019)
A new regulation on Salmonella control in Serbia has been implemented recently. The main goal is to eliminate two most common serovars, Salmonella Enteritidis (SE) and Salmonella Typhimurium (ST) from the poultry farms and to keep the infections caused by these bacteria under control. Experimental work conducted in the past decade in our Institute provided evidence that Salmonella is transmitted easily in a flock and is hard to be eliminated from the farms and hatcheries. This is in good agreement with the published research work by other authors. It is also evident that good management practice and vaccination strategy must be implemented in poultry production. Therefore a simple questionnaire for poultry producers and hatchery experts to provide a quick overview of the management practice was designed in order to find out shortcomings. Salmonella monitoring must be conducted by applying bacteriological examination while serology control is efficient more during exploitation and less during rearing. However, it was found out that bacteriology and serology can be successfully combined in order to estimate the infection status. Although regular bacteriological screening for salmonella is compulsory, some farmers in the country do not pursue this type of analysis at the recommended frequency. Subsequently, those who send the samples for bacteriological examination more often seem to have more salmonella related problems. The most frequent finding of salmonella was in the chickens that died during transportation and the first three days of life and from paper pads. Extremely rare finding of salmonella was in breeding eggs and even rarer in table eggs. If environmental samples from commercial layers are positive, serology testing is recommended. Salmonella isolated from chickens and farm premises in Serbia were susceptible to most antimicrobials tested. Multiple resistances was quite seldom but approximately 20% of the isolates were quinolone resistant. The resistance to fluoroquinolones was not detected. However, Salmonella highly resistant to nalidixic acid with MIC (minimal inhibitory concentration) to NAL > 512 mg/ml were less susceptible to ciprofloxacin, although MICs to CIP were still below the CLSI recommended breakpoint (R > 4 mg/ml). Similar reports were obtained in investigation of salmonella isolated from human stool and the research indicates that the most frequent serovar in the country in humans, food and poultry include Salmonella Enteritidis, Salmonella Typhimurium and Salmonella Infantis.